Statistical Analysis of Climate Series Analyzing, Plotting, Modeling, and Predicting with R - Pruscha, Helmut (Springer Berlin Heidelberg : Imprint: Springer, 2013)
The book presents the application of statistical methods to climatological data on temperature and precipitation. It provides specific techniques for treating series of yearly, monthly and daily records. The results' potential relevance in the climate context is discussed. The methodical tools are taken from time series analysis, from periodogram and wavelet analysis, from correlation and principal component analysis, and from categorical data and event-time analysis. The applied models are - among others - the ARIMA and GARCH model, and inhomogeneous Poisson processes. Further, we deal with a number of special statistical topics, e.g. the problem of trend-, season- and autocorrelation-adjustment, and with simultaneous statistical inference. Programs in R and data sets on climate series, provided at the author's homepage, enable readers (statisticians, meteorologists, other natural scientists) to perform their own exercises and discover their own applications.